PRODUKSI BENIH 17 VARIETAS BAWANG MERAH (Allium cepa L. var Aggregatum) DI DATARAN TINGGI PADA MUSIM HUJAN - Nurmalita Waluyo; Joko Pinilih; Ineu Sulastrini; Eli Korlina (UIN Sunan Gunung Djati Bandung, 2023)
Seeds are one of the factors that support the success of plant cultivation. This study aims to obtain information on seed production of 17 shallot varieties in the highlands during the rainy season. Research was conducted to find out the production of shallot seeds in Indonesian Vegetable Research Institute (IVEGRI) Lembang (1,250 m above sea level) from October to December 2020. The material used is in the form of 17 varieties of shallot from the IVEGRI, namely: Sembrani, Katumi, Maja Cipanas, Bima Brebes, Kuning, Pikatan, Trisula, Pancasona, Mentes, Kramat 1, Kramat 2, TSS Agrihort 1, TSS Agrihort 2, Violetta 1 Agrihorti, Violetta 2 Agrihorti, Violetta 3 Agrihorti, Ambassador 1 Agrihorti. Wet weight, dry weight of askip and seed weight per plot (15.4 m2) obtained range from 26.9 kg -58.4 kg, 18.0 kg -36.5 kg, and 10.0 kg -26.3 kg. Violetta 2 Agrihorti is the variety that produces the highest wet weight per plot, and Sembrani is the variety that produces the dry weight of askip and the highest seed weight. The ratio between the weight of the seeds planted with the seeds produced in this rainy season planting ranges from 2.6 (Sembrani) – 11.0 times (Violetta 3 Agrihorti) on average 7.1 times. The production of onion seeds can be carried out in the rainy season and is influenced by the variety.